Peningkatan Kapasitas Produksi Unit Usaha Bubur Pedas Instan “Superburdas” Melalui Penerapan Teknologi Penyiang Daun Pakis - Nopriandy, Feby; Suhendra, Suhendra; Anjiu, Leo Dedy; Erwin, Erwin (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2025)
The partner was a business unit engaged in processing instant bubur pedas with the SuperBurdas trademark. This business started in 2022 until now it has grown rapidly. The problem experienced by partners was in the process of preparing raw materials. The process of preparing raw materials, especially for vegetables, was done traditionally using human labor. This process was quite time-consuming, labor-intensive and very impractical. Based on these conditions, the implementation team offered a solution in the form of applying fern leaf weeder machine technology to partners. This service activity includes making a fern weeder machine, machine functional testing, operation and maintenance training, asset handover and activity evaluation. This activity has an impact on increasing partner knowledge and skills and increasing work capacity in the instant bubur pedas production process. The fern leaf weeder machine is able to increase the capacity of manual weeding of ferns by 0.9 kg / hour to 3.15 kg / hour when using a machine.